LncRNA MIR503HG Promotes High-Glucose-Induced Proximal Tubular Cell Apoptosis by Targeting miR-503-5p/Bcl-2 Pathway - Cao X; Fan QL (Diabetes, Metabolic Syndrome and Obesity, 2020)
Xu Cao, Qiu-Ling Fan Department of Nephrology, The First Hospital of China Medical University, Shenyang, People’s Republic of ChinaCorrespondence: Qiu-Ling FanDepartment of Nephrology, The First Hospital of China Medical University, No. 155 Nanjing Bei Street, Heping District, Shenyang 110001, People’s Republic of ChinaTel +86 13904012680Email cmufql@163.comAim: More than half of microRNAs are located in genes. LncRNAs are host genes of intronic microRNAs that regulate intracellular splicing to form pre-miRNAs that are processed to mature miRNAs. MicroRNAs work as partners or antagonists of their host lncRNAs by fine-tuning their target genes. However, whether lncRNA-MIR503HG (miR-503 host gene) is co-transcribed with miR-503 and affects miR-503 splicing, thereby affecting its target gene Bcl-2 expression and cell mitochondrial apoptotic pathway in diabetic nephropathy (DN) is currently unknown.Methods: Human proximal tubular (HK-2) cells cultured in high glucose were transfected with lncRNA MIR503HG overexpression/inhibition plasmid and miR-503 mimics/inhibitor. Real-time quantitative PCR was used to measure the expression levels of lncRNA MIR503HG, pre-miR-503, miR-503 and Bcl-2. Western blot was used to measure the protein expressions of Bcl-2, Bax, Cytc and cleaved-caspase 9/3. Annexin V/PI flow cytometry was used to measure apoptosis.Results: Host lncRNA MIR503HG was co-transcribed with miR-503. MIR503HG regulated the expression of miR-503 by affecting miR-503 splicing synthesis. In the presence of high glucose, the expression levels of lncRNA MIR503HG and miR-503 were up-regulated in HK-2 cells cultured in high glucose. Bcl-2 expression was inhibited and levels of apoptosis-related proteins Cytc and Bax were increased in HK-2 cells cultured in high glucose, all of which promoted the caspase cascade reaction, leading to increased caspase-9 and caspase-3 shear fragments inducing apoptosis of the mitochondrial pathway. Inhibition of MIR503HG led to a reduction in miR-503 expression, up-regulated its target gene Bcl-2, inhibited the expression levels of Bax and other apoptosis-related proteins and attenuated HK-2 cell apoptosis induced by high glucose. Co-transfection of miRNA-503 partially offset the effect of MIR503HG-siRNA.Conclusion: MIR503HG indirectly regulates Bcl-2 by promoting the co-transcription of miRNA-503 to participate high-glucose-induced proximal tubular cell apoptosis, providing a new target for diabetic nephropathy treatment.Keywords: diabetic nephropathy, lncRNA MIR503HG, miR-503, host gene, apoptosis